التخصيصات الأستثمارية في العراق .... هل تستهدف الفقراء ؟ (المجلة العراقية للعلوم الاقتصادية, 2018)
Poverty was not a feature in Iraq, but the Iraqi economy has been exposed to a process of systematic impoverishment, started in the eighties of the last century. فلقد ألقت الحرب العراقية الأيرانية ، والتي استمرت للفترة 1980- 1988 ، أعباءاً هائلة على الأقتصاد العراقي The Iraq-Iran war, which continued for the period 1980 - 1988, set enormous burdens on the Iraqi economy ، فقد تم تقدير خسائر العراق من الحرب العراقية الأيرانية بـ 452 بليون دولار أي ما يعادل 10 أضعاف معدل الناتج المحلي الأجمالي اثناء الحرب 1980 – 1988 ..On the other hand the sanctions imposed on Iraq under Security Council resolution 661 on August 6.1990 had massive consequences on the Iraqi economy. After 2003, the poverty continued in Iraq, due to the legacy of terrorist actions, largely on the possibility of investment in the Iraqi economy, which led to high rates of unemployment. وقد أضيف الى ذلك حالات الفساد الكبيرة في المؤسسات العراقية ، حيث تشير التقارير الدولية الى تدني موقع العراق في مؤشرات الأمان ومناخ الأستثمار فضلاً عن ذلك ما تعكسه المؤشرات الدولية من سوء مؤشر الفساد والشفافية Beside b Besides that, there is vast corruption in the Iraqi institutions, and the international reports indicate that Iraq had a low level in the indicators of security site and the investment climate. واستناداً الى نتائج المسح الأقتصادي والأجتماعي للأسرة في العراق ( والمسمى مسح IHSES ) ظهر ان المحافظات تتفاوت من حيث الفقر وشدته، ففي حين يعد أكثر من 40 % من سكان بعض المحافظات فقراء، (المثنى49 %، بابل 41%، وصلاح الدين 40 %)، فان نسبة الفقراء في محافظات أخرى تقل عن 10 % كما في محافظات إقليم كردستان. Based on the results of the Economic and Social Survey of the Family in Iraq (IHSES), it was found that Iraq's governorates vary in terms of poverty and its severity. While more than 40% of the population of some governorates is poor, for example: Muthanna 49%, Babylon 41%, and Salahuddin 40%. The proportion of poor people in other governorates is less than 10%, as in Kurdistan province. كما ان المحافظات التي ترتفع فيه نسبة الفقراء (حجم الفقر) تزداد فيها فجوة الفقر أيضا. Also, the governorates with high proportion of the poor (the size of poverty) its poverty gap is increasing as well. أن كل هذا يستدعي أن يكون هنالك قدراً من العدالة في توزيع التخصيصات الأستثمارية بين المحافظات العراقية بحيث تأخذ مستوى الفقر في المحافظات فضلاً عن عدد السكان في المحافظAll this requires some justice in the distribution of investment allocations between the Iraqi governorates to take into account the level of poverty in these governorates as well as the number of people in the province. The research aims to find an understandable and scientific way to distribute the investment allocations among the governorates of Iraq to take into account the reality of poverty and the size of population in each governorate.